903 NOVEL MALIGNANT MUTATION IN HYPERTROPHIC CARDIOMYOPATHY. (15th December 2022) - Moscardelli, Silvia; Rusconi, Daniela; Santangelo, Gloria; Bursi, Francesca; Micaglio, Emanuele; Bulfamante, Gaetano; Saponaro, Maria; Centola, Marco; Guazzi, Marco
Abstract: Background: Hypertrophic cardiomyopathy (HCM) is a common inherited disease almost invariably caused by mutations in sarcomeric genes. The HCM phenotype is clinically heterogeneous with myocyte hypertrophy, disarray, and myocardial fibrosis as histological hallmarks. This condition is recognized as an important cause of sudden cardiac death (SCD) in the youth and of heart failure (HF) in the elderly. Current guidelines mandate genetic analysis as a class I indication in HCM. Indeed, the advent of the next generation sequencing in the medical practice has led to decipher the molecular etiology of HCM and to assess the disease risk in family members with relevant insights into the clinical course. Clinical case: A 62-year-old man followed-up at another Hospital with a non-obstructive HCM diagnosis, was referred to our Hospital for therapy optimization and clinical follow-up. Past medical history included third degree atrioventricular block at age 40 treated with dual chamber pacemaker (PM) and, at age of 60, atrial flutter with high ventricular response complicated with cardiogenic shock and stroke. Due to worsening systolic function and ventricular sustained tachycardia he was upgraded to implantable cardioverter defibrillator which delivered appropriate shocks. Echocardiography performed during current hospitalization showed a moderate concentric hypertrophy (intraventricular septum 17 mm, cardiac mass index 258 g/m 2 ), dilated ventricle with reduced ejection fraction (33%) and akinesis of the mid inferior and infero-septal walls of the left ventricle and of the apex, with a stratified thrombotic apposition. Magnetic resonance was contraindicated because of non-compatible PM. Due to alteration in serum proteins and free light chain, to rule out systemic disease, extensive imaging diagnosis was performed including bone scintigraphy and abdominal ultrasonography which resulted negative. While waiting for bone marrow aspiration and biopsy the patient rapidly deteriorated with worsening renal failure, ensuing proteinuria until exitus. After an appropriate pre-test counseling the family consented to genetic test in the proband. Clinical exome sequencing revealed the presence of a missense mutation in MYH7 gene. This new mutation is characterized by the substitution of cysteine residue by a serine in 905 codon of MYH7 gene. Cys905Ser results in a semi-conservative amino acid substitution which may impact disulfide bond formation in the MYH7 protein. To date no study has described this mutation as a cause of HCM. A mutation affecting this same codon, Cys905Phe was reported in only one patient with HCM. From a biological point of view, this variant lies in the head region of the protein where the majority of the missense variants are grouped and statistically associated to HCM phenotype. Several studies reported that the occurrence of atrial fibrillation (AF) tends to be more prevalent in patients carrying the MYH7 mutation. Furthermore, AF is associated with substantial risk for HF-related mortality, stroke, and severe functional disability. Awareness regarding the spectrum of MYH7 mutations probably related to SCD or HF combined with a thorough patient characterization for molecular and clinical features, may help to improve the genotype and phenotype correlation. This important challenge could elucidate better the mechanism of HCM enabling cardiologists to a better clinical decision-making and patients' care.